Ce0.9Pr0.1O2‐δ‐Pr0.6Ca0.4MnO3‐δ dual‐phase membranes: oxygen permeability and stability. Issue 1 (22nd October 2021) - Wang, Shu; Wang, Xiaopeng; Huang, Yanhang; Zeng, Lingyong; He, Yiyi; Boubeche, Mebrouka; Luo, Huixia
Abstract: Previously unreported Ce0.9 Pr0.1 O2‐ δ ‐Pr0.6 Ca0.4 MnO3‐ δ (CPO‐PCMO) dual‐phase membrane is designed and successfully fabricated. The crystal structure, surface morphology, stability, and oxygen permeability is systematically investigated. The XRD results reveal that CPO‐PCMO dual‐phase membranes are made up of cubic fluorite phase and orthorhombic perovskite phase, which exhibit excellent stability at elevated temperature under air atmospheres as well as various low oxygen conditions such as Ar or CO2 atmospheres. In addition, no obvious holes, cracks, and impurities are observed. The obtained CPO‐PCMO membrane with 0.8 mm thickness exhibits comparable oxygen permeability with a flux of 0.23 mL min −1 cm −2 under air/He gradient at 1000 °C and stably works over 300 min without obvious deterioration under air/CO2 gradient, suggesting it has good CO2 stability. Abstract : A dual‐phase membrane composed of cubic ceria phase and orthorhombic perovskite phase is successfully synthesized. This membrane exhibits favorable stability under various atmospheres and possesses satisfactory oxygen permeability, which can work stably under air/CO2 without obvious deterioration.